Preparing (Metalla)carboranes for Nanomedicine. (19th March 2021) - Gozzi, Marta; Schwarze, Benedikt; Hey‐Hawkins, Evamarie
Abstract: "There's plenty of room at the bottom" (Richard Feynman, 1959): an invitation for (metalla)carboranes to enter the (new) field of nanomedicine. For two decades, the number of publications on boron cluster compounds designed for potential applications in medicine has been constantly increasing. Hundreds of compounds have been screened in vitro or in vivo for a variety of biological activities (chemotherapeutics, radiotherapeutics, antiviral, etc.), and some have shown rather promising potential for further development. However, until now, no boron cluster compounds have made it to the clinic, and even clinical trials have been very sparse. This review introduces a new perspective in the field of medicinal boron chemistry, namely that boron‐based drugs should be regarded as nanomedicine platforms, due to their peculiar self‐assembly behaviour in aqueous solutions, and treated as such. Examples for boron‐based 12‐ and 11‐vertex clusters and appropriate comparative studies from medicinal (in)organic chemistry and nanomedicine, highlighting similarities, differences and gaps in physicochemical and biological characterisation methods, are provided to encourage medicinal boron chemists to fill in the gaps between chemistry laboratory and real applications in living systems by employing bioanalytical and biophysical methods for characterising and controlling the aggregation behaviour of the clusters in solution. Abstract : Before we can catch biological systems in their nanometre working dimension, we have to understand them on the physical (bulk and surface), chemical and biological level. Herein, we comprehensively review the current state of research and approaches in the field of boron cluster medicinal chemistry, highlighting successful approaches, exposing challenges and appealing to standardise the heterogeneous nanomedicine field.